Social Problems Raised In “Mother to Son” Langston Hughes - Sidiqnazarova Zulfiya Mirsharapovna; Shermatov Botirjon Erkinovich (Peerian Journals Publishing, 2022)
Langston Hughes and the basic themes of his poetry. It is important to know about an idea of that period. Theoretical part of the work can be useful for the articles, diploma works in American Literature. The Practical value lies in as a source of preparation for lectures and seminars on American literature classes.
Keywords: Mother to Son; smoothness; ease; delicacy and wealth